Energy, exergy and anti-vibration assessment of microfluidic fuel cell with a novel two-phase flow model. (1st April 2021) - Ouyang, Tiancheng; Chen, Jingxian; Lu, Jie; Xu, Peihang; Mo, Chunlan
Abstract: To cope with the weaknesses of high pollution emission and poor security in traditional lead acid and lithium-ion batteries, microfluidic fuel cell plays a significant role in energy transformation instrument of high efficiency and low pollution, with potential applications in portable electronic device. For the energy conservation purpose, it is considered as an ideal power supply with prolonged work time and substantial power output. The two-phase flow and vibration effects are the two important factors to be considered in practical fuel cell applications because the gas/liquid two-phase flow is a non-negligible threat in acidic fuel cells. In this study, a two-phase flow computational model is developed to investigate the vibration effects on cell characteristics based on a multi-physics coupling process. The model accuracy is validated with the previous experiment. Major results demonstrate that: (1) Vibration intensity and frequency have negative impacts on cell performance owing to the severe fuel crossover and delayed gas phase discharge; (2) Increasing the feed liquid flow rate is a resultful approach to resist the vibration effects, alleviate fuel crossover, and improve the current and power outputs. However, these are achieved at the expense of fuel utilisation and exergy efficiency; (3) Increased contact angle also plays the positive part in decreasing gas phase fraction; (4) The cell performance depends strongly on vibration intensity, and improving the anti-seismic performance of MFC mainly increases the ability of the cell to resist vibration intensity. In conclusion, the fuel cell is a clean effective power supply device for the emission reduction and sustainable development, and the work lays the foundation for improving the shock-absorbing design and microfluidic fuel cell performance. This technology is generally applied to the portable electronic equipment, the analysis reveals the flow state of cell, and this research method is used for reference to performance analysis of other types of fuel cells. Graphical abstract: Image 1 Highlights: A two-phase model is developed for microfluidic fuel cell with flow-through anode. Performance assessment is conducted for the clean power supply development. Simulating the influences of vibration effects on the cell characteristics. Fuel utilisation and exergy efficiency are used for performance evaluation.